The mediating effect of leader-member dyadic communication style agreement on the relationship between servant leadership and group-level organizational citizenship behavior - Abu Bakar, Hassan; McCann, Robert M. (SAGE Publications, 2016)
This research examines how dyadic communication agreement in the workplace may operate at the dyadic-within group level as a process variable that mediates the relationship between servant leadership and group organizational citizenship behavior (OCB).In doing so, we propose a model of leader–member dyadic communication whereby communication style agreement mediates the relationships between servant leadership and group level OCB in work groups.The model is tested by using hierarchical linear modeling with data obtained from a sample of 510 employees and 59 work groups in three Malaysian organizations. Results show that servant leadership is related to leader–member dyadic communication style agreement in the workplace at the individual level and that the servant leadership–group-level OCB link is partially mediated by leader–member dyadic communication style agreement in the workplace. These findings partially validate our proposed model and provide empirical support for the central roles of communication exchange processes in work groups.